Seismic Illumination Analysis with One-Way Wave Propagators Coupled with Reflection/Transmission Coefficients in 3D Complex Media - Sun, Weijia; Fu, Li-Yun; Wei, Wei; Zhou, Binzhong (IntechOpen, 2011)
None